Nutritional and Hygienic Quality of Raw Milk in the Mid-Northern Region of Algeria: Correlations and Risk Factors - Soumeya Adjlane-Kaouche; Rafik Benhacine; Faiçal Ghozlane; Abderrahmane Mati (The Scientific World Journal)
This paper aims to study the overall quality of raw milk in the mid-northern region of Algeria. The analysis results showed a decrease in the average temperature for the delivery of 1,54°C with P<0.001. However, no significant variation (P>0.05) was observed in almost all the physical and nutritional parameters studied (pH, fat content, and protein content) between M1 and M2. The average contamination by total mesophilic aerobic bacteria (TMAB), coliforms, yeasts, molds, and different pathogens in samples taken at M1 showed significant changes at M2. This was confirmed by the decrease of reduction time of methylene blue (RTMB), about 54%. The variation was described as follows: (P>0.05) for yeasts and (P<0.05) for molds in M1 and M2, (P<0.05) for TMAB in M1, and (P<0.001) for TC, FC, and TMAB in M2. The analysis for the detection of Salmonella spp. showed no contamination in all samples tested, while antibiotic residues were detected in 35% of milks delivered. In conclusion, several risk factors have been identified in this study, namely, the effect of the season and the distance between the farm and the dairy unit.